(untitled) (Bangladesh Journal of Scientific and Industrial Research, 2017)
An experiment was carried out for a period of 180 days (1stApril to 30 th September) in 2015 to find out a the suitable culture technique of Notopterus chitala (Hamilton-Buchanan, 1882) in pond habitats located at the Hatchery Complex, Department of Fisheries, University of Rajshahi. The experiment was conducted under 3 treatments (T1: only feed used, T2: feed and Tilapia, T3: only Tilapia used) each with 3 replications. Mean stocking weight of Notopterus chitala was 21.4±0.27 g for all treatments. Basal fertilization was same for all the treatments (cowdung: 1235 kg/ha, urea: 50 kg/ha, TSP: 50 kg/ha). Feed (8-10% of body weight) and fertilized (weekly with cowdung 1000 kg/ha,) based farming was followed in all treatments. Mean value of water temperature varied from 32.53±0.04°C (T2) to 32.57±0.03°C (T1) to transparency 32.34±0.68 (T2) cm to 33.87±0.37cm (T3), Dissolved Oxygen 4.76±0.04mg/l (T3) to 4.91±0.04 mg/1 (T1), pH 7.62±0.03 (T1) to 7.70±0.05 (T2) , alkalinity 127.04±1.4 mg/l (T2) to 131.46±0.92 mg/1 (T3),respectively. The mean value of different growth parameters varied with the followings-final weight 380±.88 g (T1) to 645 ± .57g (T2), weight gain 358.6 ± .14g (T1) to 623.60± .02g (T2), SGR (% bwd-1) 3.84±.02 (T1) to 4.54± .01(T2).The survival rate between 93.33±6.67 % (T1) to 100 ± 0.00 %(T2), and the total production of Notopterus chitala was found 1593.2±2.46(T2) Kg/ha/180 days which was significantly higher than that of others treatments 938.6 ±31.29 (T1), 1133.7±62.98 (T3) respectively. The growth parameters are significantly different among the treatments. The total production of Tilapia was observed 1790.18±0.7(T2) kg/ha/180 days which was higher than 1584.9±0.39(T3).The combined production (Chital + Tilapia) of fish was obtained 3383.2±2.86(T2) which was higher than those of 938.6 ±31.29(T1) and 2718.6±50.1(T3) respectively.The total income raised from 394200±6.36BDT/ha (T1) to 736548±24.04 BDT/ha (T2), net profit 209180±12.49BDT/ha (T1) to 468258±17.63BDT/ha (T2) and CBR 1.13±.01 (T1) to 1.75±.02 (T2) respectively and all growth parameters were significantly (P<0.05) different among the treatments. Treatment T2 (feed and Tilapia used) was proved best in terms of production and economics of N. chitala culture in pond habitats based on experimental results. Bangladesh J. Sci. Ind. Res. 52(3), 187-194, 2017